Online Booking Of Express Bus Tickets To Beat Touts - New Straits Times, Jennifer Comez (2008)
Soon the hassle of going to crowded bus stations to book intercity tickets or paying over the odds to ticket touts during peak travel seasons will be a thing of the past.